Effect Of Metacarpal Osteotomy And Traction For Lengthening Of The Forelimb In Calves - Kumaresan A (Department of Surgery, College of Veterinary and Animal Sciences, 1998)
The study was undertaken with the objectives of evaluating the effect of osteotomy and distraction osteogenesis for lengthening of the limb and to evolve treatment measures that can be adopted for the correction of shortened limb in calves. The experimental study was conducted in 12 crossbred bull calves aged six to twelve months and weighing 60 to 120 kg, randomly divided into two groups of six animals each. Under xylazine (@ 0.2 mg/kg) sedation and brachial plexus block (two per cent lignocaine solution 10-15 ml) transverse osteotomy was performed at the mid-shaft region of the metacarpal bone. In group I the limb was immobilized using a locally fabricated full pin transverse fixation device. From the sixth day onwards, the bone fragments were retracted in opposite directions at the rate 1 mm gap/day for 10 days. In group II partial tenotomy of the flexor tendons was performed on the sixth day and immobilization and retraction procedures was adopted as in group I. Sedation with xylazine followed by brachial plexus block was found satisfactory for the surgical manipulations.